Burn Injuries Associated with At-Home Hair Braiding. Issue 3 (17th May 2022) - Shakir, Afaaf; O'Connor, Annemarie; Teele, Megan; Gottlieb, Lawrence J; Vrouwe, Sebastian Q
Abstract: Hair braiding that incorporates synthetic extensions has increased in popularity across all age groups. As part of the styling process, the ends of the braid are commonly dipped in scalding water; an increasing number of patients have presented to our center after containers of recently boiled water are accidentally tipped over and spilled onto patients. A retrospective chart review was performed of all patients who sustained burn injuries related to at-home hair braiding presenting to an ABA-verified burn center between January 1, 2006 and July 31, 2020. A total of 41 patients presented over the study period, and the frequency of this type of burn increased over time, with 54% of injuries occurring in the past 3 years (2018–2020). The mean patient age was 7.5 years, and the majority of patients were under 18 years of age (97%), female (95%), and African-American (98%). Seventy-three percent of injuries occurred in the home and 88% involved another person in the hair braiding process. The mean TBSA burned was 5% (range 1–20%). The most commonly involved areas were the back (54%), thigh/leg (37%), and neck (24%). Ninety percent were partial-thickness injuries only, with 10% having some degree of full-thickness injury. Ninety percent of patients required inpatient admission, and 34% of patients required at least one operative procedure. Hair braiding, with the use of scalding water to seal and set the ends of braids, can lead to burn injuries that require hospitalization and the need for surgical intervention.